Assessing Dietary Intake in Women: A Systematic Review of Gender-Specific Food Frequency Questionnaires - Ayşegül Kartal Acet; Zeynep Göktaş (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objective: To classify various food frequency questionnaires that have been developed and validated specifically for women.Materials and Methods: The researchers reviewed the available literature to identify food frequency questionnaires specifically developed and/or validated for non-pregnant women. To assess the validity and reproducibility of the questionnaires, correlation coefficients were examined between reference methods and FFQ estimates, as well as between repeated administrations of the same FFQs. Systematic search was conducted using PubMed, Science Direct and, Web of Science. The target of the review was the healthy non-pregnant women.Results: Fourteen eligible papers were included and analyzed in this review. The correlation coefficients between the nutrients measured by the food frequency questionnaires and the reference measurements varied between 0.11 and 0.81 for the general FFQs. All of the proposed questionnaires, except for one, proved to be valid. Among the studies, three reported high correlations (r ≥ 0.60) between FFQ estimates and the reference measure, seven presented moderate correlations (r = 0.40-0.59), two had fair correlations (r = 0.30-0.39), and one had poor correlations (r < 0.3) for certain nutrients derived from the FFQs. Design and validation issues such as portion-size estimation, correlation coefficients and, quality assessment scores were highlighted.Conclusions: There are existing, validated food frequency questionnaires (FFQs) designed specifically for assessing women's nutritional intake; however, more research is necessary. Future studies should focus on creating FFQs that are tailored to specific goals, taking into account factors like age, gender, and ethnicity.